LIQUIDITY AND CAPITAL ANALYSIS OF STATE-OWNED BANKS IN INDONESIA BASED ON OJK REGULATIONS (POJK) - Purnamasari, Keti; Windarti, Gusti Ayu Oka (Jurnal Manajemen, 2024)
This study analyzes liquidity and capitalization based on the Financial Services Authority Regulation (POJK). Liquidity is measured by LCR and NSFR based on POJK Number 42/POJK.03/2015 concerning the obligation to fulfill the Liquidity Coverage Ratio (LCR) for Commercial Banks and POJK Number 50/POJK.03/2017 concerning the obligation to fulfill the Net Stable Funding Ratio (NSFR) for Commercial Banks. Capitalization is measured using the KPMM ratio according to the risk profile based on POJK Number 11/POJK.03/2016 concerning the obligation to provide minimum capital for Commercial Banks. The samples used in this study were state-owned banks listed on the Indonesia Stock Exchange, namely PT Bank Rakyat Indonesia Tbk (BBRI), PT Bank Mandiri Tbk (BMRI), PT Bank Negara Indonesia Tbk (BBNI), and PT Bank Tabungan Negara Tbk (BBTN). The data used are secondary data in the form of Bank annual reports, LCR calculation reports, and NSFR Reports for the 2019 to 2023 Period of each Bank. The four state-owned banks have LCRs of more than 100%. This indicates that the banks have highly liquid assets that are sufficient to handle a liquidity stress scenario within a 30-day period. The four state-owned banks have NSFRs of more than 100%. This indicates that the institutions have sufficient stable funding to meet funding needs for the next 12 months. The four state-owned banks have CARs that exceed the CAR limit based on the risk profile rating of each bank. The higher the CAR, the better the bank's ability to meet its financial obligations when under pressure